Influência da natureza e topografia da superfície na micro-abrasão e micro-abrasão-corrosão - Ardila, Miguel Angel Narvaez (2017)
The aim of this work is to contribute to the understanding of the effect of surface characteristics on abrasive wear with and without corrosive effect. The micro-abrasion-corrosion apparatus developed at the Tribology and Materials Laboratory (LTM) was used. The following tests were used: AISI 304 austenitic stainless steel test specimens (body), silica abrasive particles and rotational speed of 150 rpm. For the corrosive analysis, an 1N H2SO4 electrolytic solution was used. For the influence of the surface topography of the specimen, the AISI 304 steel was grinded using silicon carbide (SiC) (#80 and # 4000), and tested with perpendicular and parallel arrangements with respect to the direction of rotation of the sphere. Zirconia balls (Ø 25.4 mm) were used as counter bodies. In order to analyze the influence of the nature and topographic evolution of the counter-body surface, five spherical counter bodies (Ø 25.4 mm) were used in the micro-abrasion tests: one ceramic (silicon nitride, Si3N4), one metal (AISI steel 52100) and three thermoplastic polymers (polypropylene, PP, polyacetal, POM and polyamide 6.6, PA 6.6); For the micro-abrasion-corrosion tests one ceramic (silicon nitride) and one thermoplastic polymer (PP) were used. The topographic evolution of the counter bodies was monitored along the tests through interferometry and profilometry. The grooving of the abrasive particles was predominant in the wear scars generated in all tests performed. The surface topographies of the body and counter-body showed to have relation with the wear rate in the micro-abrasion and micro-abrasion-corrosion tests. Higher roughness parameters induced higher wear rates, and show greater sensitivity in micro-abrasion-corrosion. It was attributed that higher values of the roughness parameters achieved greater effectiveness in the drag and participation of abrasive particles in the contact.